Paternal preconceptional diet enriched with n-3 polyunsaturated fatty acids affects offspring brain function in mice - Li, Muhan; Shi, Qiaoyu; Jiang, Xueyi; Liu, Xuanyi; Han, Wei; Fan, Xiuqin; Li, Ping; Qi, Kemin (Frontiers in Nutrition, 2022)
Recent studies demonstrate that paternal nutrition prior to conception may determine offspring development and health through epigenetic modification. This study aims to investigate the effects of paternal supplementation of n-3 polyunsaturated fatty acids (n-3 PUFAs) on the brain development and function, and associated gene imprinting in the offspring. Three to four-week-old male C57BL/6J mice (founder) were fed with an n-3 PUFA-deficient diet (n-3 D), and two n-3 PUFA supplementation diets - a normal n-3 PUFA content diet (n-3 N) and a high n-3 PUFA content diet (n-3 H) for 12 weeks. Then they were mated to 10-week-old virgin female C57BL/6J mice to generate the offspring. The results showed that paternal n-3 PUFA supplementation in preconception reduced the anxiety- and depressive-like behavior, and improved sociability, learning and memory in the offspring, along with increased synaptic number, upregulated expressions of neuron specific enolase, myelin basic protein, glial fibrillary acidic protein, brain-derived neurotrophic factor in the hippocampus and cerebral cortex, and altered expressions of genes associated with mitochondria biogenesis, fusion, fission and autophagy. Furthermore, with paternal n-3 PUFA supplementation, the expression of imprinted gene Snrpn was downregulated both in testes of the founder mice and their offspring, but upregulated in the cerebral cortex and hippocampus, with altered DNA methylation in its differentially methylated region. The data suggest that higher paternal intake of n-3 PUFAs in preconception may help to maintain optimal brain development and function in the offspring, and further raise the possibility of paternal nutritional intervention for mental health issues in subsequent generations.